1999
DOI: 10.1046/j.1365-2923.1999.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients as teachers: a qualitative study of patients' views on their role in a community-based undergraduate project

Abstract: The study has shown that patients see themselves clearly as having specific contributions to make to medical students' education and training. This has implications for the further development of community-based teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
138
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(157 citation statements)
references
References 10 publications
11
138
2
Order By: Relevance
“…Typically, therapeutic patient's education offered by health care professionals helps the patients to learn and to develop numerous competencies, to adapt behaviors leading to an improvement of different health parameters, including bio-markers and quality of life [66]. On the other way around, patients can also, and in fact, are more and more involved in medical and recovery-oriented training [6,67,68]. At the UR as a concept, patients and medical students can study and experiment attitudes like empathy, altruism, rigor or reflexivity together through mentorship and reciprocal, positive emulation (as per the above mentioned CanMEDS).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, therapeutic patient's education offered by health care professionals helps the patients to learn and to develop numerous competencies, to adapt behaviors leading to an improvement of different health parameters, including bio-markers and quality of life [66]. On the other way around, patients can also, and in fact, are more and more involved in medical and recovery-oriented training [6,67,68]. At the UR as a concept, patients and medical students can study and experiment attitudes like empathy, altruism, rigor or reflexivity together through mentorship and reciprocal, positive emulation (as per the above mentioned CanMEDS).…”
Section: Discussionmentioning
confidence: 99%
“…Service staff reported that they saw the overall benefit of implementing consumer participation and in particular valued having the voice of someone who actually uses, or has previously used the service, to better understand how the service was perceived. Consumer involvement in other health sectors, such as mental health, has contributed to a range of improvements, including the increase of service accessibility, and providing psychosocial benefits to consumers [10,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Organisational and logistical issues of recruitment and retention of participating families Although evidence suggests that patients who participate in medical education are positive about the experience, 11,12 recruitment can be diffi cult. In the Family Study, recruitment is dependent on the co-operation of third parties and can therefore be unpredictable.…”
Section: Challenges Implementing This Teaching Methods Includementioning
confidence: 99%